2000
DOI: 10.1007/bf02703938
|View full text |Cite
|
Sign up to set email alerts
|

Role of polyamines and ethylene as modulators of plant senescence

Abstract: Under optimal conditions of growth, senescence, a terminal phase of development, sets in after a certain physiological age. It is a dynamic and closely regulated developmental process which involves an array of changes at both physiological and biochemical levels including gene expression. A large number of biotic and abiotic factors accelerate the process. Convincing evidence suggests the involvement of polyamines (PAs) and ethylene in this process. Although the biosynthetic pathways of both PAs and ethylene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
148
0
9

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(161 citation statements)
references
References 78 publications
4
148
0
9
Order By: Relevance
“…This correlation represents a feedback of the inhibition of the enzyme action in one pathway and of enzyme activation in the other pathway (Pandey et al 2000). Ethylene inhibited the activities of arginine decarboxylase and SAM decarboxylase thus reducing PAs contents (Bouchereau et al 1999).…”
Section: Discussionmentioning
confidence: 98%
“…This correlation represents a feedback of the inhibition of the enzyme action in one pathway and of enzyme activation in the other pathway (Pandey et al 2000). Ethylene inhibited the activities of arginine decarboxylase and SAM decarboxylase thus reducing PAs contents (Bouchereau et al 1999).…”
Section: Discussionmentioning
confidence: 98%
“…S-adenosyl methionine (SAM) is the precursor molecule to both polyamines and ethylene (Langebartels et al, 1991;Pandey et al, 2000), both of which are thought to be involved in the response to ozone (Langebartels et al, 1991;Overmyer et al, 2005). It is of interest, therefore, that SAM Synthetase (SAMS) co-located to QTL for both late and early season visible damage on LG II.…”
Section: Genes With Differential Expression Between Ozone Sensitivitymentioning
confidence: 99%
“…It is of interest, therefore, that SAM Synthetase (SAMS) co-located to QTL for both late and early season visible damage on LG II. Pandey et al (2000) put forward a hypothesis for the interacting role of polyamines and ethylene in the control of senescence, with ethylene acting as a positive regulator and polyamines as a negative regulator. The authors suggested a model in which polyamine and ethylene biosynthetic pathways Table 5 50 most significant differentially expressed genes in common to P. deltoides and P. trichocarpa after exposure to 9 hrs 200 nL L À1 ozone.…”
Section: Genes With Differential Expression Between Ozone Sensitivitymentioning
confidence: 99%
“…Polyamines form a class of aliphatic amines that are ubiquitous in living organisms and are known to have role in a wide range of biological processes including plant growth and development (Pandey et al, 2000). Putrescine, spermidine and spermine are the major forms of polyamines which are biosynthesised from orginine or ornithine.…”
Section: Issn: 2319-7706 Volume 6 Number 8 (2017) Pp 481-493mentioning
confidence: 99%